DAMPAK KARAKTERISTIK DEWAN DIREKSI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Doddy Setiawan; Ratna Tri Hapsari; Anas Wibawa (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. This research aims at examining the effect of board of directorscharacteristics on corporate social responsibility disclosure using Indonesia miningindustry context. Indonesia use two tier board system: board of directors and board ofcommissioners. Board of directors engage in management work and board ofcommissioners supervise board of directors. This study focus on board of directorscharacteristics: gender, tenure, board size and percentage of foreign directors. Sampleof the study consists of listed firm in mining sectors at Indonesia Stock Exchange(IDX). There are 106 observations from 2013 – 2015 period. This study use GRI indexto measure corporate social responsibility disclosure. The result of the study shows thatforeign directors have negative effect on the corporate social responsibility. This resultshows that foreign directors might not have positive effect on how mining firm disclosecorporate social responsibility disclosure. Further, gender and board of directors sizehave positive effect on corporate social responsibility. Woman as chief executiveofficer provide better disclosure on corporate social responsibility. However, tenurehave no significant effect on corporate social disclosure using Indonesian context.